Production of clavulanic acid and cephamycin C by Streptomyces clavuligerus under different fed-batch conditions - Bellão, C.; Antonio, T. [UNESP]; Araujo, Maria Lucia Gonsales da Costa [UNESP]; Badino, A. C. (Brazilian Society of Chemical Engineering, 2013)
The effect of carbon source and feeding conditions on the production of clavulanic acid (CA) and cephamycin C (CephC) by Streptomyces clavuligerus was investigated. In fed-batch experiments performed with glycerol feeding, production of CA exceeded that of CephC, and reached 1022 mg.L-1. Highest CephC production (566.5 mg.L-1) was obtained in fed-batch cultivation with glycerol feeding. In fed-batch experiments performed with starch feeding, the production of CephC was in general higher than that of CA. A dissociation index (DI) was used to identify feeding conditions that favored production of CephC relative to CA. In all cultures with glycerol, DI values were less than unity, indicating higher production of CA compared to CephC. Conversely, in cultures fed with starch, the DI values obtained were greater than unity. However, no carbon source or feeding condition was able to completely dissociate the production of CA from that of CephC.
Keywords: Streptomyces clavuligerus; Clavulanic acid; Cephamycin C; Fed-batch